2021
DOI: 10.3906/sag-2007-131
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and prevalence of concomitant chemo-radiotherapy-induced oral mucositis in patients with oral squamous cell carcinoma

Abstract: Background/aim Quantification of oral mucositis that progresses during concomitant chemo-radiotherapy (CCRT) is essential for its management. It is important to determine the methods that are simple, reliable and beneficial in foreseeing mucositis at earlier stages of treatment. Materials and methods A prospective study was conducted on 100 oral cancer patients receiving CCRT following the inclusion criteria. Patients were evaluated for mucositis i.e. erythema and ulcer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…18 In a study by Igor et al, oral mucositis was observed in men with a rate of 78.2%. 19 In our study, the incidence rate of grade III mucositis in men was 53%. Luo et al found the most common toxicity with chemoradiotherapy in NPC were grade III or IV oral mucositis (40%), pharyngo-esophagitis (12%), leukopenia (29.6%) and neutropenia (26.4%).…”
Section: Discussionmentioning
confidence: 44%
“…18 In a study by Igor et al, oral mucositis was observed in men with a rate of 78.2%. 19 In our study, the incidence rate of grade III mucositis in men was 53%. Luo et al found the most common toxicity with chemoradiotherapy in NPC were grade III or IV oral mucositis (40%), pharyngo-esophagitis (12%), leukopenia (29.6%) and neutropenia (26.4%).…”
Section: Discussionmentioning
confidence: 44%
“…On the contrary, Minhas et al . (2021)[ 15 ] reported tongue to be the most predominant site for the occurrence of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…But in addition to systemic symptoms, patients frequently have oral health problems such as candidiasis, gingivitis, ulcers, xerostomia, accumulation of plaque, dysphagia, and dysgeusia. These oral health issues are very likely to have a signi cant negative impact on quality of life, both psychologically in the form of anxiety, and sadness and functionally in the form of di culty in speaking, and masticating food [10,11].…”
Section: Introductionmentioning
confidence: 99%